Impact Assessment of Phosphogypsum Leachate on Groundwater of Sfax-Agareb (Southeast of Tunisia): Using Geochemical and Isotopic Investigation - Samira Melki; Moncef Gueddari (Journal of Chemistry)
The production of phosphoric acid by the Tunisian Chemical Group, in Sfax, Tunisia, led to the degradation of the groundwater quality of the Sfax-Agareb aquifer mainly by the phosphogypsum leachates infiltration. Spatiotemporal monitoring of the quality of groundwater was carried out by performing bimonthly sampling between October 2013 and October 2014. Samples culled in the current study were subject to physicochemical parameters measurements and analysis of the major elements, orthophosphates, fluorine, trace metals, and stable isotopes (18O, 2H). The obtained results show that the phosphogypsum leachates infiltration has a major effect on the downstream part of the aquifer, where the highest values of conductivity, SO42-, Ortho-P, and F-, and the lowest pH were recorded. In addition, these results indicated that phosphogypsum leachates contained much higher amount of Cr, Cd, Zn, Cu, Fe, and Al compared to the groundwater. Spatiotemporal variation of the conductivity and concentrations of major elements is linked to the phosphogypsum leachates infiltration as well as to a wide range of factors such as the natural conditions of feeding and the water residence time. Contents of O18 and 2H showed that the water of the Sfax-Agareb aquifer undergoes a large scale evaporation process originated from recent rainfall.